Failure of activation of striatum during the performance of executive function tasks in adult patients with bipolar disorder. Issue 4 (2nd March 2020) - Tian, Fangfang; Diao, Wei; Yang, Xun; Wang, Xiuli; Roberts, Neil; Feng, Can; Jia, Zhiyun
Abstract: Background: Although numerous studies have used functional neuroimaging to identify executive dysfunction in patients with bipolar disorder (BD), the findings are not consistent. The aim of this meta-analysis is to identify the most reliable functional anomalies in BD patients during performance of Executive Function (EF) tasks. Methods: A web-based search was performed on publication databases to identify functional magnetic resonance imaging studies of BD patients performing EF tasks and a voxel-based meta-analytic method known as anisotropic Effect Size Signed Differential Mapping (ES-SDM) was used to identify brain regions which showed anomalous activity in BD patients compared with healthy controls (HC). Results: Twenty datasets consisting of 463 BD patients and 484 HC were included. Compared with HC, BD patients showed significant hypo-activation or failure of activation in the left striatum ( p = 0.00007), supplementary motor area (BA 6, p = 0.00037), precentral gyrus (BA 6, p = 0.0014) and cerebellum (BA 37, p = 0.0019), and hyper-activation in the left gyrus rectus (BA 11, p ≈ 0) and right middle temporal gyrus (BA 22, p = 0.00031) during performance of EF tasks. Sensitivity and subgroup analyses showed that the anomaly of left striatum is consistent across studies and present in both euthymic and BD I patients. Conclusions: Patients with BD consistently showed abnormal activation in the cortico-striatal system during performance of EF tasks compared with HC. Failure of activation of the striatum may be a reliable marker for impairment in performance of especially inhibition tasks by patients with BD.